PENGARUH SENAM PILATES TERHADAP PENURUNAN NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER II DAN III - Wulandari, Rizky; Fatimah, Siti Nur (Prodi Fisioterapi UFDK, 2023)
Pregnancy is a condition where a woman is pregnant and lasts for about 40 weeks. When women enter the second and third trimesters, they will experience enlarged stomachs and changes in body structure which cause certain complaints. One of the most common complaints experienced by pregnant women is back pain. One way to deal with lower back pain is to do Pilates. Pilates is a recovery method that aims to improve the coordination and balance of the muscles in the body, focusing on the pelvic and abdominal muscles. This research seeks to investigate how pilates exercises impact the reduction of lower back pain in pregnant women during the second and third trimesters of pregnancy. This study used an experimental design with measurements before and after treatment for 3 weeks, with an intervention frequency of 2 times a week. The total sample involved was 22 pregnant women who experienced lower back pain. Pain was measured using a visual analogue scale, before and after the intervention. The data obtained were analyzed by statistical tests using the Shapiro-Wilk Test, and then the Wilcoxon Signed Rank Test. The findings indicated that the data did not follow a normal distribution, and the Wilcoxon Signed Rank Test revealed a p=0.000, signifying a beneficial impact of pilates exercise in alleviating lower back pain among pregnant women during their second and third trimesters before and after the interventionKeywords: Pregnancy, Lower Back Pain, Pilates Exercise.